O3 catalytic oxidation foam metal-based Cu-Mn catalyst and preparation method thereof
By using O3 catalytic oxidation of foam metal-based Cu-Mn catalysts, the problems of poor stability and mass transfer properties of existing catalysts are solved, and more efficient catalytic reactions and lower treatment costs are achieved.
Patent Information
- Application Number
- CN202411848383.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-21
AI Technical Summary
The catalysts in the existing O3 catalytic oxidation process have poor stability performance, poor mass transfer performance, and the catalysts are prone to deactivate, resulting in poor catalytic performance and high treatment costs.
O3 catalytic oxidation of foam metal-based Cu-Mn catalyst is used, which consists of foam metal, a support deposited on the foam metal, and CuO and MnO2 supported on the support, and is prepared by electrophoretic deposition, sintering and impregnation and lifting.
The stability and mass transfer properties of the catalyst are improved, the catalytic reaction is rapid, the treatment cost is low, and 95% of nitrobenzene can be removed under neutral pH conditions.
Abstract
Description
Technical Field
[0001] The invention relates to a catalyst and a preparation method thereof, in particular to an O3 catalytic oxidation foam metal-based Cu-Mn catalyst and a preparation method thereof. Background Art
[0002] O3 catalytic oxidation is a chemical reaction process that uses ozone (O3) as an oxidant. Ozone is a strong oxidant that can react with a variety of organic and inorganic substances to purify water, air or treat industrial wastewater. During the catalytic oxidation process, ozone is accelerated to decompose under the action of the catalyst to generate highly reactive hydroxyl radicals, which react with pollutants to convert them into harmless or low-toxic substances. O3 catalytic oxidation technology has been widely used in the field of environmental engineering due to its high efficiency, rapidity and wide range of applications. It is one of the mainstream technologies for pollutant control in the future.
[0003] At present, the catalysts commonly used in the O3 catalytic oxidation process include powder catalysts, ceramsite catalysts and honeycomb ceramic catalysts, which have poor stability performance, poor mass transfer performance, and the catalysts are easily deactivated, resulting in poor catalytic performance and increased processing costs. Summary of the invention
[0004] The purpose of the present invention is to solve the problems that the catalyst commonly used in the existing O3 catalytic oxidation process technology has poor stability and mass transfer performance, and the catalyst is easily deactivated, resulting in poor catalytic performance and high processing cost, and to provide an O3 catalytic oxidation foam metal-based Cu-Mn catalyst and a preparation method thereof. The technical scheme is as follows:
[0005] An O3 catalytic oxidation foam metal-based Cu-Mn catalyst, comprising a foam metal, a carrier deposited on the foam metal, and CuO and MnO2 loaded on the carrier; wherein the foam metal is a three-dimensional permeable structure, and the carrier is Al 2 O 3 and TiO 2 .
[0006] The method for preparing O3 catalytic oxidation foam metal-based Cu-Mn catalyst is achieved by the following steps:
[0007] a. Pre-treating the foam metal and pure aluminum powder respectively;
[0008] b. Mix 500-1000 parts of anhydrous ethanol, 0.2-1 parts of aluminum isopropoxide and 5-12 parts of pretreated pure aluminum powder by mass, and use the mixture as electrophoresis liquid after ultrasonic oscillation for 4-5 hours;
[0009] c. Inject the electrophoresis solution into the electrophoresis tank, use the pretreated foam metal as the cathode and graphite as the anode, the distance between the two electrodes is 10 mm, and perform electrophoretic deposition for 2 to 5 minutes;
[0010] d. After deposition, the cathode was taken out and dried at room temperature for 12 hours. Then, it was sintered in a nitrogen atmosphere at 700-900°C for 8-12 hours, cooled to room temperature, and then taken out. Then, it was calcined in an air atmosphere at 400-600°C for 6-10 hours, cooled to room temperature, and then taken out. Al 2 O 3 / Foam metal;
[0011] e. Ti(OC 4 H 9 ) 4 , C 2 H 5 OH and H 2 O are mixed in a volume ratio of 4:16:1 to obtain TiO 2 Sol, then Al 2 O 3 / Foam metal on TiO 2 The sol was immersed and pulled for 1 to 8 times, and then taken out, dried, and calcined at 400 to 600 ° C for 4 to 8 hours to obtain TiO 2 / Al 2 O 3 / Foam metal;
[0012] f. TiO 2 / Al 2 O 3 / The foamed metal is placed in a mixed solution of copper nitrate, manganese nitrate and oxalic acid solution in a mass ratio of 1-2:4-6:100-200, and is dipped and pulled for 1-8 times, taken out and dried at room temperature for 24 hours, and then calcined at 400-600°C for 4-8 hours to obtain an O3 catalytic oxidation foamed metal-based Cu-Mn catalyst;
[0013] The foamed metal in step a is a three-dimensional transparent structure; the drying temperature in step e is 80-100° C.; and the mass concentration of the oxalic acid solution in step f is 4-6%.
[0014] The O3 catalytic oxidation foam metal-based Cu-Mn catalyst provided by the present invention has a three-dimensional permeable structure, high three-dimensional permeability, small pressure drop, good catalytic performance, low processing cost, stability performance improved by 30% to 50%, mass transfer performance improved by 20% to 45%, and rapid catalytic reaction; the O3 catalytic oxidation foam metal-based Cu-Mn catalyst provided by the present invention is used in O3 catalytic oxidation process technology, and is tested to be able to remove up to 95% of nitrobenzene under neutral pH conditions. DETAILED DESCRIPTION
[0015] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any combination of the specific implementation modes.
[0016] Specific implementation method 1: In this implementation method, the Cu-Mn foam metal-based catalyst for O3 catalytic oxidation is composed of a foam metal, a carrier deposited on the foam metal, and CuO and MnO2 loaded on the carrier; wherein the foam metal is a three-dimensional permeable structure, and the carrier is Al 2 O 3 and TiO 2 .
[0017] Specific implementation method 2: In this implementation method, the method for preparing O3 catalytic oxidation foam metal-based Cu-Mn catalyst is implemented by the following steps:
[0018] a. Pre-treating the foam metal and pure aluminum powder respectively;
[0019] b. Mix 500-1000 parts of anhydrous ethanol, 0.2-1 parts of aluminum isopropoxide and 5-12 parts of pretreated pure aluminum powder by mass, and use the mixture as electrophoresis liquid after ultrasonic oscillation for 4-5 hours;
[0020] c. Inject the electrophoresis solution into the electrophoresis tank, use the pretreated foam metal as the cathode and graphite as the anode, with the distance between the two electrodes being 10 mm, and perform electrophoretic deposition for 2 to 5 minutes.
[0021] d. After deposition, the cathode was taken out and dried at room temperature for 12 hours. Then, it was sintered in a nitrogen atmosphere at 700-900°C for 8-12 hours, cooled to room temperature, and then taken out. Then, it was calcined in an air atmosphere at 400-600°C for 6-10 hours, cooled to room temperature, and then taken out. Al 2 O 3 / Foam metal;
[0022] e. Ti(OC 4 H 9 ) 4 , C 2 H 5 OH and H 2 O are mixed in a volume ratio of 4:16:1 to obtain TiO 2 Sol, then Al 2 O 3 / Foam metal on TiO 2 The sol was immersed and pulled for 1 to 8 times, and then taken out, dried, and calcined at 400 to 600 ° C for 4 to 8 hours to obtain TiO 2 / Al 2 O 3 / Foam metal;
[0023] f. TiO2 / Al 2 O 3 / The foamed metal is placed in a mixed solution of copper nitrate, manganese nitrate and oxalic acid solution in a mass ratio of 1-2:4-6:100-200, and is dipped and pulled for 1-8 times, taken out and dried at room temperature for 24 hours, and then calcined at 400-600°C for 4-8 hours to obtain an O3 catalytic oxidation foamed metal-based Cu-Mn catalyst;
[0024] The foamed metal in step a is a three-dimensional transparent structure; the drying temperature in step e is 80-100° C.; and the mass concentration of the oxalic acid solution in step f is 4-6%.
[0025] In this embodiment, the pretreatment of the foam metal is to use H with a mass concentration of 10%. 2 SO 4 The solution is cleaned at 80-90°C, and then the foam metal is rinsed with deionized water until the pH value of the outflowing water is 7, and then dried at 100°C for 1 hour; the pretreatment removes stains and grease on the surface of the foam metal and makes the surface of the metal wire rough.
[0026] In this embodiment, the pretreatment of pure aluminum powder is to use 1wt% ammonia solution to wash, then rinse the pure aluminum powder with deionized water until the pH value of the outflowing water is 7, and dry naturally; the pretreatment removes the oxide layer of the pure aluminum powder.
[0027] In this embodiment, the TiO obtained in step e 2 / Al 2 O 3 / Al in foam metal 2 O 3 With TiO 2 The mass ratio of CuO to MnO2 is 10-25:75-90; the molar ratio of CuO to MnO2 in the O3 catalytic oxidation foam metal-based Cu-Mn catalyst obtained in step f is 1-4:3-12.
[0028] Specific embodiment 3: This embodiment differs from specific embodiment 2 in that in step a, 550 parts of anhydrous ethanol, 1 part of aluminum isopropoxide and 10 parts of pretreated pure aluminum powder are mixed by mass and ultrasonically vibrated for 4.5 hours. Other steps and parameters are the same as those of specific embodiment 2.
[0029] Specific embodiment 4: This embodiment differs from specific embodiment 2 in that the electrophoretic deposition in step c is performed for 5 minutes. The other steps and parameters are the same as those in specific embodiment 2.
[0030] Specific embodiment 5: This embodiment differs from specific embodiment 2 in that in step d, the sintering is performed under nitrogen atmosphere at 800°C for 10 hours, then the sintering is performed in the furnace and cooled to room temperature, and then the sintering is performed in air atmosphere at 500°C for 8 hours, then the sintering is performed in the furnace and cooled to room temperature. The other steps and parameters are the same as those of specific embodiment 2.
[0031] Specific implementation method 6: This implementation method is different from the specific implementation method 2 in that in step e, Al 2 O 3 / Foam metal on TiO 2 The sol was immersed and pulled for 5 times, and then taken out, dried and calcined at 500° C. for 6 hours. The other steps and parameters were the same as those in the second embodiment.
[0032] Specific implementation method 7: This implementation method is different from the specific implementation method 2 in that the drying temperature in step e is 90° C. The other steps and parameters are the same as those in the specific implementation method 2.
[0033] Specific embodiment eight: This embodiment differs from specific embodiment two in that in step f, the catalyst is immersed and pulled four times in a mixed solution of copper nitrate, manganese nitrate and oxalic acid solution in a mass ratio of 1.8:4.5:100, and then dried at room temperature for 24 hours, and then calcined at 500°C for 5 hours to obtain an O3 catalytic oxidation foam metal-based Cu-Mn catalyst. The other steps and parameters are the same as those in specific embodiment two.
[0034] The O3 catalytic oxidation foam metal-based Cu-Mn catalyst obtained in this embodiment is used in the O3 catalytic oxidation process technology. It has been tested that 66% of nitrobenzene can be removed under neutral pH conditions.
[0035] Specific embodiment 9: This embodiment is different from specific embodiment 2 in that in step f, the catalyst is immersed and pulled three times in a mixed solution of ammonium metavanadate, ammonium tungstate and oxalic acid solution in a mass ratio of 1.4:4.8:150, and then dried at room temperature for 24 hours, and then calcined at 500°C for 4 hours to obtain an O3 catalytic oxidation foam metal-based Cu-Mn catalyst. The other steps and parameters are the same as those in specific embodiment 2.
[0036] The O3 catalytic oxidation foam metal-based Cu-Mn catalyst obtained in this embodiment is used in the O3 catalytic oxidation process technology. It has been tested that it can remove 70% of nitrobenzene under neutral pH conditions.
[0037] Specific embodiment 10: This embodiment is different from the specific embodiment 2 in that in step f, the catalyst is immersed and pulled twice in a mixed solution of ammonium metavanadate, ammonium tungstate and oxalic acid solution in a mass ratio of 1.2:5.5:20, and then dried at room temperature for 24 hours, and then calcined at 500°C for 6 hours to obtain an O3 catalytic oxidation foam metal-based Cu-Mn catalyst. The other steps and parameters are the same as those in the specific embodiment 2.
[0038] The O3 catalytic oxidation foam metal-based Cu-Mn catalyst obtained in this embodiment is used in the O3 process technology. It has been tested that 81% of nitrobenzene can be removed under neutral pH conditions.
[0039] Specific implementation eleven: This implementation differs from specific implementation two in that the mass concentration of the oxalic acid solution in step f is 5%. The other steps and parameters are the same as those in specific implementation two.
[0040] Specific embodiment 12: The method for preparing O3 catalytic oxidation foam metal-based Cu-Mn catalyst in this embodiment is implemented according to the following steps: a. Pre-treat the foam metal and pure aluminum powder respectively; b. Mix 1000 parts of anhydrous ethanol, 1 part of aluminum isopropoxide and 12 parts of pre-treated pure aluminum powder by mass, and use them as electrophoresis liquid after ultrasonic oscillation for 4 hours; c. Inject the electrophoresis liquid into the electrophoresis tank, use the pre-treated foam metal as the cathode, graphite as the anode, and the distance between the two electrodes is 10mm, and perform electrophoretic deposition for 2 minutes; d. After deposition, take out the cathode, dry it at room temperature for 12 hours, and then sinter it in a nitrogen atmosphere at 800°C for 10 hours, then cool it to room temperature with the furnace and take it out, and then place it in an air atmosphere at 500°C for 8 hours, and then cool it to room temperature with the furnace and take it out to obtain Al 2 O 3 / foam metal carrier; e. Ti(OC 4 H 9 ) 4 , C 2 H 5 OH and H 2 O are mixed in a volume ratio of 4:16:1 to obtain TiO 2 Sol, then Al 2 O 3 / Foam metal supports on TiO 2 The sol was dipped and pulled twice, taken out and dried, and then calcined at 500℃ for 6h to obtain TiO 2 / Al 2 O 3 / foam metal carrier; f, copper nitrate, manganese nitrate and oxalic acid solution are mixed in a mass ratio of 15::100 to obtain a mixed solution, and then TiO 2 / Al 2 O 3 / The foam metal carrier module is immersed and pulled in the mixed solution once, taken out and dried at room temperature for 24 hours, and then calcined at 500°C for 5 hours to obtain an O3 catalytic oxidation foam metal-based Cu-Mn catalyst; wherein the foam metal base in step a is a three-dimensional transparent structure; the drying temperature in step e is 90°C; the mass concentration of the oxalic acid solution in step f is 5%.
[0041] The O3 catalytic oxidation foam metal-based Cu-Mn catalyst obtained in this embodiment has been tested to have a stability performance improved by 46.5% and a mass transfer performance improved by 43.2%; the obtained O3 catalytic oxidation foam metal-based Cu-Mn catalyst is used in O3 process technology, and it has been tested that 95% of nitrobenzene can be removed under neutral pH conditions.
Claims
1. An O3 catalytic oxidation foam metal-based Cu-Mn catalyst, characterized in that: The O3 catalytic oxidation foam metal-based Cu-Mn catalyst is composed of foam metal, a carrier deposited on the foam metal, and CuO and MnO2 loaded on the carrier; the foam metal is a three-dimensional transparent structure, and the carrier is Al2O3 and TiO2.
2. A method for preparing a foamed metal-based Cu-Mn catalyst for O3 catalytic oxidation, characterized in that: The method for preparing O3 catalytic oxidation foam metal-based Cu-Mn catalyst is achieved by the following steps: a. Pre-treating the foam metal and pure aluminum powder respectively; b. Mix 500-1000 parts of anhydrous ethanol, 0.2-1 parts of aluminum isopropoxide and 5-12 parts of pretreated pure aluminum powder by mass, and use the mixture as electrophoresis liquid after ultrasonic oscillation for 4-5 hours; c. Inject the electrophoresis solution into the electrophoresis tank, use the pretreated foam metal as the cathode and graphite as the anode, the distance between the two electrodes is 10 mm, and perform electrophoretic deposition for 2 to 5 minutes; d. After deposition, the cathode is taken out, dried at room temperature for 12 hours, then sintered at 700-900°C in a nitrogen atmosphere for 8-12 hours, then cooled to room temperature with the furnace and taken out, then calcined at 400-600°C in an air atmosphere for 6-10 hours, then cooled to room temperature with the furnace and taken out to obtain Al2O3 / foam metal; e. Mix Ti(OC4H9)4, C2H5OH and H2O in a volume ratio of 4:16:1 to obtain TiO2 sol, then immerse Al2O3 / foam metal in the TiO2 sol and pull it 1 to 8 times, take it out, dry it, and then calcine it at 400 to 600°C for 4 to 8 hours to obtain TiO2 / Al2O3 / foam metal; f. Place TiO2 / Al2O3 / foam metal in a mixed solution of copper nitrate, manganese nitrate and oxalic acid solution in a mass ratio of 1-2:4-6:100-200, immerse and pull for 1-8 times, take out and dry at room temperature for 24 hours, and then place at 400-600°C for 4-8 hours to obtain O3 catalytic oxidation foam metal-based Cu-Mn catalyst; The foamed metal in step a is a three-dimensional transparent structure; the drying temperature in step e is 80-100° C.; and the mass concentration of the oxalic acid solution in step f is 4-6%.
3. The method for preparing O3 catalytic oxidation foam metal-based Cu-Mn catalyst according to claim 2, characterized in that: In step a, 550 parts of anhydrous ethanol, 1 part of aluminum isopropoxide and 10 parts of pretreated pure aluminum powder are mixed by mass and ultrasonically vibrated for 4.5 hours.
4. The method for preparing O3 catalytic oxidation foam metal-based Cu-Mn catalyst according to claim 2, characterized in that: In step c, the electrophoretic deposition was performed for 5 min.
5. The method for preparing O3 catalytic oxidation foam metal-based Cu-Mn catalyst according to claim 2, characterized in that: In step d, the product is sintered in a nitrogen atmosphere at 800° C. for 10 h, then cooled to room temperature in the furnace and taken out, and then sintered in an air atmosphere at 500° C. for 8 h, then cooled to room temperature in the furnace and taken out.
6. The method for preparing O3 catalytic oxidation foam metal-based Cu-Mn catalyst according to claim 2, characterized in that: In step e, the Al2O3 / foam metal substrate is immersed and pulled in the TiO2 sol for 5 times, taken out, dried, and then calcined at 500°C for 6 hours.
7. The method for preparing O3 catalytic oxidation foam metal-based Cu-Mn catalyst according to claim 2, characterized in that: The drying temperature in step e is 90°C.
8. The method for preparing O3 catalytic oxidation foam metal-based Cu-Mn catalyst according to claim 2, characterized in that: In step f, the mixture is immersed and pulled in a mixed solution of copper nitrate, manganese nitrate and oxalic acid solution in a mass ratio of 1.8:4.5:100 for 4 times, taken out and dried at room temperature for 24 hours, and then calcined at 500°C for 5 hours to obtain an O3 catalytic oxidation foam metal-based Cu-Mn catalyst.
9. The method for preparing O3 catalytic oxidation foam metal-based Cu-Mn catalyst according to claim 2, characterized in that: In step f, the catalyst is immersed and pulled twice in a mixed solution of copper nitrate, manganese nitrate and oxalic acid solution in a mass ratio of 1.2:5.5:20, taken out and dried at room temperature for 24 hours, and then calcined at 500°C for 6 hours to obtain an O3 catalytic oxidation foam metal-based Cu-Mn catalyst.
10. The method for preparing O3 catalytic oxidation foam metal-based Cu-Mn catalyst according to claim 2, characterized in that: The mass concentration of the oxalic acid solution in step f is 5%.